Pemberdayaan Masyarakat Melalui RT Sehat di Desa Gumirih Kecamatan Singojuruh Kabupaten Banyuwangi - Nur Anim Jauhariyah; Ahmad Mufarih Hasan Fadly; Mahmudah Mahmudah (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2018)
The purpose of this service is to trigger the Gumirih Village community in Singojuruh Subdistrict to be able to implement healthy life by throwing garbage not carelessly. The method used in this empowerment uses participatory Action Research methods. The results of observations in the field, especially in Gayam Lor Hamlet, the community dumped garbage in the river and still did bathing, washing, and defecating in the river. After learning about the various shortcomings in Gumirih Village, with a lack of public awareness about environmental hygiene, lack of facilities to support cleanliness, training was held and inviting residents to eliminate the culture of throwing garbage in the river, and inviting residents to beautify the environment around the house to grow comfortable looking at the beautiful environment as soon as the desire to dispose of garbage or defecate in the river is diminishing. Things that should be appreciated in this cleaning program are cohesiveness of citizens, cleanliness of the environment, and the beauty of the environment of the hamlet road.